Non-Muslim Indian Scholar to Islamic Studies: A Study of Narendra Nath Law’s Treatise - Javed Akhatar (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2023)
Muslims arriving from the subcontinent wanted for learning and teaching Islam in India, especially in history. Ulema and Indian Muslim scholars have contributed a lot in this realm, and the study of Islam has been an area of great interest to non-Muslim writers. Their role in this subject is also of great worth, and their contributions, to name a few, include the translation of the Quran, Seerat, Islamic teachings, Tasawwuf, Muslim history and civilization, and their society and culture. The present Paper is an endeavor to bring a brilliant contribution of the same kind in the field of Islamic Studies to the fore made by a distinguished Indian non-Muslim scholar, Mr. Narendra Nath Law, with special reference to his noted book “Promotion of Learning in India: during Muhammadan Rule (by Muhammadans).” This Paper gives three sections, and the first gives a brief sketch of the book; the second critically reviews the sources on which the content of the book is based; and the third treats with depth investigation and analysis of the views and assumptions of Mr. Law on educational and literary history in India during the long roll of Muslim rulers. The importance of the Paper lies in its focus on the history of learning and teaching Islam in India. By highlighting the contributions of Law, the Paper aims to shed light on the significant role played by non-Muslim scholars in the study of Islam in India, which has often been overlooked.